Effect of Nanosized Tin Oxide Layer on the Efficiency of Photovoltaic Processes in Film Solar Cells Based on Cadmium Telluride - G.S. Khrypunov; O.V. Pirohov; D.A. Kudiy; R.V. Zaitsev; A.L. Khrypunova; V.A. Gevorkyan; P.P. Gladyshev (Журнал нано- та електронної фізики)
The influence of the thickness of the nanosized layer on the efficiency of photoelectric processes in solar cells (SC) ITO / SnO2 / CdS / CdTe / Cu / Au formed on different substrates was investigated. For device structures formed on the glass substrates, the maximum efficiency of 11.4 % is achieved when thickness of the tin oxide layer is 80 nm. For flexible solar cells formed on a polyimide film, the maximum efficiency of 10.8 % is observed when thickness of the tin oxide layer is 50 nm. This paper discusses the physical mechanisms of the observed differences in efficiency.